AFFECT STUDENT CAREER DECISIONS INTERNSHIP AND ENTREPRENEURSHIP COURSES - Ida Nurlaeli (Brilliant International Journal Of Management And Tourism, 2023)
The main purpose of this study was to analyze the impact of an entrepreneurial course and internship on management students at the State Islamic University of Sunan Gunung Djati's career decisions. This information was gathered from surveys given to former participants and current participants in the 2022 cohort of the State Islamic University of Sunan Gunung Djati Bandung's Management Study Program. A total of 109 respondents were included in the sample using a straightforward random sampling procedure. The results of this data analysis, which used partial least squares analysis, showed that the internship variable had a positive and significant effect on the career decision variable, but that the entrepreneurship course variable and the organizational experience variable did not.